Comparison of 2D simulations of detached divertor plasmas with divertor Thomson measurements in the DIII-D tokamak. (August 2017) - Rognlien, T.D.; McLean, A.G.; Fenstermacher, M.E.; Groth, M.; Jaervinen, A.E.; Joseph, I.; Lasnier, C.J.; Meyer, W.; Moser, A.; Porter, G.D.; Umansky, M.V.
Highlights: Two-dimensional plasma/neutral transport simulations of the scrape-off-layer/divertor plasma are compared with Divertor Thomson scattering measurements for DIII-D H-mode discharges. Experimental inner/outer divertor plasma and radiation profile asymmetries resulting from changing the direction of the toroidal magnetic field are qualitatively reproduced by the simulations. Steady-state detached plasma solutions are found when increasing the midplane separatrix density beyond a critical value, and that density is within 35% of the experimental measured separatrix density for detachment. The critical density depends on the impurity radiation and pumping models. Abstract: A modeling study is reported using new 2D data from DIII-D tokamak divertor plasmas and improved 2D transport model that includes large cross-field drifts for the numerically difficult low anomalous transport regime associated with the H-mode. The data set, which spans a range of plasma densities for both forward and reverse toroidal magnetic field ( Bt ), is provided by divertor Thomson scattering (DTS). Measurements utilizing X-point sweeping give corresponding 2D profiles of electron temperature ( Te ) and density ( ne ) across both divertor legs for individual discharges. The simulations focus on the open magnetic field-line regions, though they also include a small region of closed field lines. The calculations show the same features of in/out divertor plasma asymmetries as measured in the experiment, with the normal Bt direction (ion ∇ B drift toward the X-point) having higher ne and lower Te in the inner divertor leg than outer. Corresponding emission data for total radiated power shows a strong inner-divertor/outer-divertor asymmetry that is reproduced by the simulations. These 2D UEDGE transport simulations are enabled for steep-gradient H-mode conditions by newly implemented algorithms to control isolated grid-scale irregularities.